Web-based k-Anonymization System in a Distributed Environment - Kim, Tae-Su; Kim, Jong Wook (Journal of Digital Contents Society, 2019)
Today we live in the era of Big Data. The ever increasing integration of IoT and mobile devices in many fields is resulting into generation of enormous volumes of data on daily basis. The importance of managing and distributing this big volumes of data is also increasingly growing. Big data contains a lot of information, some of which are personal and sensitive, and can result into violation of personal privacy incases of data leakage. Anonymizing big data is one of the several ways aimed at improving data security and privacy protection during data leakage scenarios. k-anonymization is one of the several techniques used for data anonymization. In this paper, we present a k-anonymization system which provides a suitable web environment for users to anonymize their data. The user generalizes the data by inputting a data delimiter and a taxonomy tree. Based on the generalization data, the k-anonymization option value is set and transmitted to the server via the web. When the k-anonymization option is passed to the server, the master server requests k-anonymization from multiple worker nodes through a distributed environment. After k-anonymization, users can download the output and share and distribute k-anonymized data. KCI Citation Count: 0